Building a Better Mathematics Classroom - Dewan, Hridaya Kant (Voices of Teachers and Teacher Educators, 2016)
This Paper focuses on the holistic teaching-learning process for Mathematics as embedded in the current thinking on Mathematics education which argues for the child building her own understanding through the process of engagement with concepts in different ways including having opportunities to collectively construct definitions and examine and modify them, developing formulas or/and algorithms, proofs and solving new problems, building patterns and generalisation, creating and setting problems and puzzles, talking and expressing mathematical concepts in written form, etc.